Prevalence and Risk Factors for Ocular Surface Disease among Patients Treated over the Long Term for Glaucoma or Ocular Hypertension. Issue 1 (January 2013) - Baudouin, Christophe; Renard, Jean-Paul; Nordmann, Jean-Philippe; Denis, Philippe; Lachkar, Yves; Sellem, Eric; Rouland, Jean-François; Jeanbat, Viviane; Bouée, Stéphane
Purpose: To determine the prevalence of ocular surface diseases and identify risk factors in a population of patients receiving antiglaucomatous eyedrops over the long term. Methods: An observational cross-sectional study was designed to investigate ocular surface signs and symptoms using simple clinical tools. An ocular surface disease intensity score was calculated based on 10 questions regarding ocular surface symptoms and signs with a 4-grade scale. Patients were classified into 3 groups (A, B, and C) according to this total score. A multinomial logistic regression was performed in order to identify risk factors for surface disease. Results: In an overall population of 516 patients, 49% belonged to group A, 30% to group B, and 21% to group C. The multivariate analysis showed that the following factors were correlated with the severity of ocular surface disease: patient age, number of daily eyedrops, past topical treatment changes for ocular intolerance (found in the history of 40% of the patients), intraocular pressure (found to be significantly higher in patients with more severe ocular surface disease), and glaucoma severity. Conclusions: Patients treated for primary open-angle glaucoma or ocular hypertension often have ocular surface diseases, more often and more severely in older patients receiving more drugs and presenting with more severe glaucoma. These high prevalence values might therefore have consequences on the burden of the disease in terms of adherence to treatment and quality of life.